Optimization of mixed botanical insecticides from Azadirachta indica and Calophyllum soulattri against Spodoptera frugiperda using response surface methodology - Syahputra Edy; Dono Danar; Sudarjat; Hidayat Yusup; Puspasari Lindung Tri; Dewi Vira Kusuma; Ishmayana Safri; Widayani Neneng Sri (Open Agriculture)
The ratio of ingredients in the mixture of botanical insecticides affects the insecticide activity. This study conducted a single and mixed insecticide test of Azadirachta indica and Callophylum soulattri against Spodoptera frugiperda. Insecticide application used the residue method on leaves with a microsyringe and acetone + methanol solvent (4:1). The test concentration was based on the preliminary tests. Optimization of the ratio between A. indica and C. soulattri was carried out using response surface methods. The test results showed that the LC50 and LC95 values of the single insecticides A. indica and C. soulattri were 0.099, 0.420 and 0.537, 3.481%, respectively. The response surface method optimization showed that the ratio between A. indica and C. soulattri resulted in the highest mortality and the lowest feed consumption at 2.0800:1.1657. The LC50 and LC95 values of the mixed insecticide were 0.030 and 0.224%, respectively. The mixed insecticide of A. indica and C. soulattri has strong synergy at LC50 and weak synergy at LC95. The mixed insecticides of A. indica and C. soulattri can be used as an alternative environmentally friendly control against S. frugiperda in maize fields.